2020
DOI: 10.1136/bmjdrc-2019-000939
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diabetes and prediabetes prevalence and predictors by HbA1c in a population from sub-Saharan Africa with a high proportion of anemia: a prospective cross-sectional study

Abstract: IntroductionEpidemiological data about diabetes mellitus (DM) for sub-Saharan Africa (SSA) are scarce and the utility of glycated hemoglobin (HbA1c) to diagnose DM is uncertain in African populations with a high proportion of anemia.Research design and methodsIn a cross-sectional study, age-adjusted prevalence rates and predictors for DM and pre-DM were prospectively assessed by HbA1c in a semirural walk-in population of Tanzania (n=992). Predictors for DM were calculated by logistic regression. Correlations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…In the present study we found an overall of Prediabetes of 9.19%. This was within the estimated global prevalence range of 4.8%-11.9% but slightly higher than that of sub-Saharan Africa alone [14].However another study that assessed the prevalence of Prediabetes based on correlation with HbA1c in sub Saharan Africa found a prevalence of 25% by the ADA criteria [12]. The ADA criteria on the other hand is known to estimate higher prevalence of Prediabetes than the WHO criteria that we used in the current study.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study we found an overall of Prediabetes of 9.19%. This was within the estimated global prevalence range of 4.8%-11.9% but slightly higher than that of sub-Saharan Africa alone [14].However another study that assessed the prevalence of Prediabetes based on correlation with HbA1c in sub Saharan Africa found a prevalence of 25% by the ADA criteria [12]. The ADA criteria on the other hand is known to estimate higher prevalence of Prediabetes than the WHO criteria that we used in the current study.…”
Section: Discussionsupporting
confidence: 65%
“…In Africa, few studies were carried out on the subject, with prevalences of 3.5 to 26.5% for T2DM and 20.2 to 43.5% for PD, among adults with HIV on ART [24]. In Sub-Saharan Africa, data on T2DM are scarce and the high prevalence of anemia compromises the usefulness of glycated hemoglobin in the diagnosis of dysglycemia [25]. The prevalence of T2DM and PD in our study was higher than that found in the literature, probably because it is a sample with a CA equal to or greater than 60 years and the majority presenting premature aging [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies examining the relation between HbA 1c and anaemia have generally focused on anaemia classified solely using haemoglobin levels, or iron-deficiency anaemia (defined using additional measures including ferritin and transferrin)-which commonly causes microcytic anaemia 9,16,[20][21][22] [S3-S5]. The majority of these studies have reported inverse associations or correlations between HbA 1c levels and such measures that are generally small in magnitude 9,16 [S3, S4].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, few studies have been based in African populations, with mixed evidence regarding the presence, direction and magnitude of associations between anaemia and HbA 1c . [20][21][22] This points to the need for further, comprehensive evidence from this region. The exact mechanisms by which different types of anaemia may affect HbA 1c are not clear, with multiple proposed hypotheses regarding pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation